State Management in Large-Scale Enterprise Frontends: Choosing Between NgRx, Redux, and Pinia (Global Journal of Computer Science and Technology, 2025)
This article examines the evolution of state management solutions in large-scale enterprise frontend applications focusing on NgRx Angular Redux React and Pinia Vue Beginning with the conceptual shift from MVC to Flux Redux patterns the article explores how each framework-specific implementation addresses complex state challenges through different architectural approaches NgRx leverages RxJS to create a reactive state system aligned with Angular s design philosophy while Redux has evolved through Redux Toolkit to improve developer experience while maintaining its core principles Pinia represents Vue s modern approach emphasizing simplicity and developer experience without sacrificing power Through comparative analysis of architectural patterns performance characteristics and developer experience metrics the article provides decision frameworks for enterprise architects selecting appropriate state management solutions based on framework alignment application complexity and team dynamics The analysis extends beyond theoretical comparisons to include practical implementation considerations identifying key trade-offs in complexity versus flexibility initial development speed versus long-term maintainability and framework-specific optimizations that impact both runtime performance and developer productivity across the application lifecycle from initial architecture to ongoing maintenance and feature expansion
Keywords: state management; enterprise applications; Redux; NgRx; Pinia